The effectiveness of instructional design according to whole brain theory of Herman in the achievement of chemistry of the fifth scientific students (Journal Of Educational and Psychological Researches, 2017)
The research aimed to identify the effectiveness of instructional design according to whole brain theory of Herman in the achievement of chemistry at the fifth scientific students at a secondary school of the General Directorate for Educational in Diyala / Baladruz in Iraq. The research sample Consisted of (57 student, (29) students as experimental group studied according to instructional design strategies for whole brain theory of Herrmann and (28) a student as a control group studied by the usual way for two semesters, a prepared achievement test as article and objective type of multiple choice, the coefficient stability of alpha-Cronbach equation reached (0.86). The research Results showed the presence of a statistically significant difference between the experimental and control groups for the experimental group and the size of a large effect.